Crop Establishment Methods Affect Plant Stand and Yield of Lentil under Rice-lentil Cropping at Khumaltar Condition - Neupane, Reshama; Bhattarai, Rajendra Kumar; Gyawaly, Pankaj; Chaulagain, Bhimsen; Kaduwal, Sangita; Karki , Tika Bahadur; Das, Soni Kumari (Agronomy Journal of Nepal, 2024)
Lentil variety Maheswor Bharati was evaluated in three establishment methods: relay, conventional tillage after rice harvest (post-rice CT), seeding by seed drill where seeds covered by minimum soil disturbance in single pass, and two rice residue heights: residue removed i.e., straw cut at 5 cm height and 30 cm residue retained at Agronomy Farm, Khumaltar from 2016/17 to 2018/19. Experiments were conducted in Randomized Complete Block design with four replications. Seeds broadcasted on standing rice during 2-16 November for relay crop; and 21-29 November for post-rice CT. Seed rates were 40 kg ha-1 for machine and manual line sowing and 50 kg ha-1 for broadcasting. Rice was harvested at 14-18 days after lentil relay. Fertilizers were applied based on soil fertility of experimental field. Significant variation was observed in plant stand, crop duration, growth and yield parameters among establishment methods; and year to year variation was also significant except for plant stand. Plant stand was greater (58-62 m-2) in machine sowing with or without residue retention and manual line sowing in post-rice CT, while low (32-40 m-2) in broadcasting methods either as relay or post-rice CT. Crop grew tall in relay with residue retained and machine sowing (41 cm) as compared to broadcasting in post-rice CT (33 cm). Grain yield was 46-115% and 24-83% higher in seeding by machine as compared to relay sown without residue (492 kg ha-1) and broadcasting in post-rice CT (578 kg ha-1), respectively.